1988
DOI: 10.1002/jhet.5570250503
|View full text |Cite
|
Sign up to set email alerts
|

Color and constitution. Part 8. Some novel dyestuffs containing indoxyl residues

Abstract: Novel dyes containing C‐likned indoxyl residues are prepared by two routes: (a) by the reaction of C‐electrophiles with N‐acetylindoxyl and (b) by the reaction of active methylene compounds with 2‐chloroindole‐3‐one. The visible absorption spectra are recorded and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…1 Its synthesis is remarkably easy; a simple one-step condensation reaction between indoxyl acetate and an aldehyde furnishes the chromophore in good yields. 46,47 Despite the long time hemiindigo has been known, the ease of its synthesis, and earlier studies of spectral properties, its photoreactions have only much later been scrutinized. These studies showed a rather complex photochemistry with [2 + 2]cycloadditions 48,49 or triplet generation 49 as possible reaction pathways in the excited state.…”
Section: Applicationsmentioning
confidence: 99%
“…1 Its synthesis is remarkably easy; a simple one-step condensation reaction between indoxyl acetate and an aldehyde furnishes the chromophore in good yields. 46,47 Despite the long time hemiindigo has been known, the ease of its synthesis, and earlier studies of spectral properties, its photoreactions have only much later been scrutinized. These studies showed a rather complex photochemistry with [2 + 2]cycloadditions 48,49 or triplet generation 49 as possible reaction pathways in the excited state.…”
Section: Applicationsmentioning
confidence: 99%
“…It is known as a chromophore for more than 100 years and was first described by Adolf von Baeyer in 1883 naming the compounds obtained from condensation of indoxylic acid and aldehydes “Indogenide” . Despite its facile synthesis, , established spectroscopic properties, and relation to hemithioindigo and aurone, the photochemistry of hemiindigo is essentially unexplored especially with regard to applications as a photoswitch. As the absorption profile of unsubstituted hemiindigo resides partially in the visible part of the electromagnetic spectrum, the possibility of reversible double bond photoisomerization using exclusively visible light is highly tempting.…”
Section: Introductionmentioning
confidence: 99%
“…21,27,43 For instance, while the reaction of the appropriate 3-oxoacid anilides with oxalyl A new route leading to dyestuffs 39, containing a pyrrolidine-2,3,5-trione moiety, was described by Katritzky. 44 The novel, colored indoxyl derivative 39 was prepared by reaction of 3,4-dichloro-N-phenylmaleinimide (38) and N-acyl indolin-3-one 37 (Scheme 12). The obtained compound is black in the solid state, but violet-reddish in solution.…”
Section: Synthesis Of Schiff Bases At C-6 Of Pyrrolidine-235-trionementioning
confidence: 99%